Ultrafiltration Lactic Acid Bacteria (LAB) in mung Beans Broth by Mixed LAB Culture - Aspiyanto, Aspiyanto; Susilowati, Agustine (Biopropal Industri, 2014)
Increasing Lactic Acid Bacteria (LAB) concentration in fermented broth of mung beans by mixed culture of Lactobacillus sp. and Streptococcus thermophillus through ultrafiltration (UF) (20,000 MWCO) at flow rate of ~8.87 L/min, room temperature and pressure 5 and 7 bars for 0, 30, 60, 90 and 120 minutes was performed. The results showed that pressure and time affected on UF performance, total solids, total protein and total number of LAB. Optimal time at pressure 5 bar was reached 60 minutes with flux 11.94 L/m2.hour, total solids 13.9423%, total protein 8.95%, total LAB 6.18 log CFU/mL, Robs of total solids 3.45%, total proteinÂ  58.67%, LAB 100% and DC 1.38 folds. The best time at 7 bar was reached 30 minutes with flux 16.16 L/m2.hour, total solids 12.2879%, total protein 4.41%, total LAB 6.04 Log CFU/mL, Robs of total solids 11.98%, total protein 45.76%, LAB 99.5 and DC 1.16 folds.